PENGARUH VARIETAS DAN BAHAN ORGANIK YANG BERBEDA TERHADAP BOBOT 1000 BUTIR DAN BIOMASSA PADI SAWAH IP 400 PADA MUSIM TANAM I - Daniel Siregar; Posma Marbun; Purba Marpaung (Jurnal Agroekoteknologi, 2013)
The objective of this study is to determine the effect of rice varieties and different organic matter ofrice fields in one growing season to the 1000 grain weight and paddy rice biomass IP 400. Theresearch was conducted at paddy fields located at UPT Main Rice Seed Big of Pasar MiringTanjung Morawa Subdistrict, Deli Serdang District. This study uses a randomized block design(RBD) with two factors, namely rice varieties Inpari I and Ciherang and organic matter. Eachtreatment consisted of non-organic material, composted straw, cow manure.The results showed thatthe use of varieties of very significant effect on the dry weight of 1000 grain rice planting season IP400 I, and the very significant effect on rice biomass IP 400. Treatment of organic material verysignificant effect on the dry weight of 1000 grain rice IP 400 in the first growing season, and a verysignificant effect terhdap rice biomass IP 400. Interaction between rice varieties and application oforganic manures no significant effect on the dry weight of 1000 grains and rice biomasaa IP 400.Keywords: IP 400, 1000 grain weight, biomass rice